Physiological and transcriptome analysis of Candida albicans in response to X33 antimicrobial oligopeptide treatment - Lu, Qunlin; Wang, Yuanxiu; Liao, Xing; Zhou, Fu; Zhang, Bin; Wu, Xiaoyu (Frontiers in Cellular and Infection Microbiology, 2023)
Candida albicans is an opportunistic pathogenic fungus, which frequently causes systemic or local fungal infections in humans. The evolution of its drug-resistant mutants necessitates an urgent development of novel antimicrobial agents. This study explored the antimicrobial activity and inhibitory mechanisms of X33 AMOP against Candida albicans strain ATCC 12322 using transcriptomic analysis. The oxford cup test results showed that X33 AMOP had strong inhibitory activity against C. albicans, and its MIC and MFC were 0.625 g/L and 2.5 g/L, respectively. Moreover, SEM and TEM showed that X33 AMOP disrupted the integrity of the C. albicans cell membrane. The AKP, ROS, H2O2 and MDA contents increased, while the reducing sugar, soluble protein, and pyruvate contents decreased after the X33 AMOP treatment. This indicated that X33 AMOP could damage the mitochondrial integrity of the cells, thereby disrupting the energy metabolism by inducing oxidative stress in C. albicans. Furthermore, transcriptome analysis showed that X33 AMOP treatment resulted in the differential expression of 1140 genes, among which 532 were up-regulated, and 608 were down-regulated. These differentially expressed genes were related to protein, nucleic acid, and carbohydrate metabolism, and their expression changes were consistent with the changes in physiological characteristics. Moreover, we found that X33 AMOP could effectively inhibit the virulence attributes of C. albicans by reducing phospholipase activity and disrupting mycelium formation. These findings provide the first-ever detailed reference for the inhibitory mechanisms of X33 AMOP against C. albicans and suggest that X33 AMOP is a potential drug candidate for treating C. albicans infections.